أثر إرساء البعدين الأخلاقي والإنساني لتفعيل الأداء الاجتماعي للمؤسسات دراسة ميدانية بمجمع صيدال : The impact of establishing the moral and human dimensions for activating the institutions social performance – A field study at Saidal Complex – - زواوي فضيلة; شدري معمرسعاد; بوزيدة حميد (Journal of North African Economies, 2025)
This study aimed to define and evaluate the impact of the institutions to the ethical and human dimensions on social performance, and then to know this effect in practice by conducting a case study in Saidal Complex, according to a descriptive analytical approach and after analyzing Data using statistical tools and the SPSS.V25 program. It was seen the presence of the ethical and humanitarian dimensions on activating the social performance of Saidal Complex. Improving social performance is achieved by integrating ethical responsibility into the organization’s strategy, as it helps it improve its reputation and achieve an added value to it, and directs employees’ behavior in accordance with work ethics and enhances their efficiency and effectiveness. as Institution of Citizenship.